Catalysing the People's Economy in the Era of Global Transformation: Innovation and Digitalization of MSMEs - Irwan Adimas Ganda Saputra; Waspodo Tjipto Subroto; Norida Candra Sakti; Angga Martha Mahendra (International Journal of Economics, Management and Accounting, 2024)
This research employs a Systematic Literature Review (SLR) to investigate the involvement of MSMEs in supporting people economy focusing on inclusiveness, innovation, and digitalization aspects and explores the primary challenges faced by MSMEs towards accessing technology and innovating for global market. This study clearly has significant implications, including that MSMEs play a key role in driving people's economy; notably most of these developing countries whose economies have reached steady state growth periods and also create jobs—results also. Regular posts of new-generation features is another factor that causes the figure to grow, something innovation and digitalization have also worked on in order to drive an efficiency curve further upward. Second, numerous obstacles encountered by MSMEs parties such as infrastructure issues are still less evenly distributed, access to capital constraints for MSMEs actors and complexities in the regulation for MSMEs actors. This study is useful for supporting the government to design adequate regulations and policies that can drive people economy through accommodating of MSME actors in the capital market as efficient prospective fund Chanel.